A Study on The Preferred Teleworking Policy by The Private Sector and Its Implication to The Demand on Transport Infrastructure (Case Study: Greater Jakarta Area) - Alvinsyah, Alvinsyah; Hadian, Edy; Syahputra, Wahyu Aji (CSID Journal of Infrastructure Development, 2023)
This study examines the implementation of a teleworking policy with a work-from-home (WFH) scheme from a private company perspective and its implications on the Greater Jakarta’s proposed urban rail network’s carrying capacity. Using descriptive and inferential statistical analyses, a representative percentage of employees capable of working from home was determined. This figure, found to be sixty percent, was then employed in a macro transport model simulation to assess its impact on urban rail network demand. The results of the statistical analysis indicate that sixty percent of the company's workforce can still permitted to work remotely. The model simulation conducted indicates that with this the sixty percent reduction in working trips utilizing transit, the proposed urban rail network plan experiences insignificant alterations in the required carrying capacity. This finding highlights the resilience of the current urban rail network plans against substantial shifts in working patterns and provides insights for future urban transport planning in the context of evolving work modalities.